Stress-mediating inflammatory cytokine profiling reveals unique patterns in malaria and typhoid fever patients - MacDonald Bin Eric; Palmer Masumbe Netongo; Severin Donald Kamdem; Christine Nzuno; Ange Maxime Tchoutang; Tchoupe Kamoua Eric Berenger; Bongkiyung Donald Buri; Ngum Leslie Ngum; Jean Paul Chedjou; Akindeh Mbu Nji; Wilfred Fon Mbacham (PLoS ONE, 2025)
Malaria and typhoid fever pose significant health risks, leading to severe morbidity and mortality when inadequately treated. Understanding the role of stress-related inflammatory cytokines is crucial, as they mediate immune responses that affect pathogen clearance and recovery. This study investigated the cytokine profiles in patients with malaria and/or typhoid fever attending the Obala District Hospital in Yaoundé, Cameroon. We conducted a cross-sectional observational study measuring cortisol and inflammatory cytokines in blood samples from 55 infected patients and a control group of 15 healthy individuals using ELISA kits. We also evaluated psychological stress over the past 30 days using a 10-item Perceived Stress Scale (PSS) questionnaire to explore the link between stress and immune response. Psychological stress levels were notably higher in the typhoid fever group (18.20 ± 5.5) compared to the other groups, although these differences were statistically insignificant. Cortisol levels were significantly elevated (p < 0.001) across all patient groups compared to controls, with the typho-malaria group demonstrating a 2.5-fold increase. Notably, cytokine levels were elevated in patients with malaria and typhoid comorbidity, particularly IL-1β, IL-2, TNF-α, and IFN-γ. While IL-6 concentrations were significantly higher in malaria and typho-malaria co-infected patients, IL-10 levels were reduced in the typho-malaria group but remained elevated compared to controls. The TNF-α/IL-10 ratio was significantly higher in the co-infected group, suggesting a heightened inflammatory response. Additionally, there was a positive correlation between perceived stress scores and IL-2 (r = 0.365, p = 0.002), IFN-γ (r = 0.248, p = 0.03), and IL-6 (r = 0.412, p = 0.0001) in the typho-malaria group. Beyond IL-6, no significant correlations were observed between stress indices and the anti-inflammatory cytokines IL-4 (r = 0.204, p = 0.09) and IL-10 (r = 0.153, p = 0.20) among co-infected individuals. These results suggest that stress response may play a crucial role in shaping the inflammatory landscape during malaria and typhoid fever. Exposure to severe stressors may disrupt immune response and contribute to negative health outcomes. Understanding the immunopathogenesis of these diseases could potentially pave the way for the development of novel therapeutic strategies targeting the stress-cytokine axis.